Genome-Wide Analysis Reveals the Potential Role of MYB Transcription Factors in Floral Scent Formation in Hedychium coronarium - Abbas, Farhat; Ke, Yanguo; Zhou, Yiwei; Yu, Yunyi; Waseem, Muhammad; Ashraf, Umair; Wang, Chutian; Wang, Xiaoyu; Li, Xinyue; Yue, Yuechong; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2021)
The MYB gene family is one of the largest groups of transcription factors (TFs) playing diverse roles in several biological processes. Hedychium coronarium (white ginger lily) is a renowned ornamental plant both in tropical and subtropical regions due to its flower shape and strong floral scent mainly composed of terpenes and benzenoids. However, there is no information available regarding the role of the MYB gene family in H. coronarium. In the current study, the MYB gene family was identified and extensively analyzed. The identified 253 HcMYB genes were unevenly mapped on 17 chromosomes at a different density. Promoter sequence analysis showed numerous phytohormones related to cis-regulatory elements. The majority of HcMYB genes contain 2-3 introns and motif composition analysis showed their functional conservation. Phylogenetic analysis revealed that HcMYBs could be classified into 15 distinct clades and the segmental duplication events played an essential role in the expansion of the HcMYB gene family. Tissue-specific expression patterns of HcMYB genes displayed spatial and temporal expression. Furthermore, seven HcMYB (HcMYB7/8/75/79/145/238/248) were selected for further investigation. Through RT-qPCR, the response of candidates HcMYB genes towards jasmonic acid methyl ester (MeJA), abscisic acid (ABA), ethylene, and auxin was examined. Yeast one-hybrid (Y1H) assays revealed that candidate genes directly bind to the promoter of bottom structural volatile synthesis genes (HcTPS1, HcTPS3, HcTPS10, and HcBSMT2). Moreover, yeast two-hybrid (Y2H) assay showed that HcMYB7/8/75/145/248 interact with HcJAZ1 protein. In HcMYB7/8/79/145/248-silenced flowers, the floral volatile contents were decreased and downregulated the expression of key structural genes, suggesting that these genes might play crucial roles in floral scent formation in H. coronarium by regulating the expression of floral scent biosynthesis genes. Collectively, these findings indicate that HcMYB genes might be involved in the regulatory mechanism of terpenoids and benzenoid biosynthesis in H. coronarium.